Fracture strength and hybrid layer formation of endodontically-treated teeth after dental bleaching photoactivated with violet LED - de Almeida, Eran Nair Mesquita [UNESP]; Victorino, Keli Regina [UNESP]; Besegato, João Felipe; Costa, Joatan Lucas de Sousa Gomes; Leandrin, Thais Piragine [UNESP]; Vitória, Matheus Sousa [UNESP]; de Andrade, Marcelo Ferrarezi [UNESP]; Kuga, Milton Carlos [UNESP] (Elsevier, 2023)
Objective: To evaluate in vitro the effect of dental bleaching using high concentration hydrogen peroxide (HP) photoactivated with violet LED on fracture strength and hybrid layer formation. Methods: forty endodontically-treated bovine teeth were randomized into four groups (n = 10): C - Control, HP – 35% hydrogen peroxide, HP-BL - 35% hydrogen peroxide photoactivated with blue LED, HP-VL - 35% hydrogen peroxide photoactivated with violet LED. Three bleaching sessions with an interval of 7 days between them were performed. After 10 days of the last bleaching session, the dental crowns were restored and submitted to the fracture strength test. Five specimens from each group were used to evaluate the hybrid layer formation by scanning electron microscope (SEM) images. One-way ANOVA and Kruskal-Wallis test were used for parametric and non-parametric data, respectively. Significance level of 5% was adopted to all the tests. Results: No differences on fracture strength among the groups were observed (p > 0.05). HP and HP-BL showed alterations on hybrid layer formation compared to C group (p < 0.05), but not for HP-VL (p > 0.05). No differences on hybrid layer formation were observed among HP, HP-VL and HP-BL groups (p > 0.05). Conclusion: Dental bleaching, photoactivated or not, did not affect the fracture strength of endodontically-treated teeth. Regardless of the protocol used, hydrogen peroxide altered the hybrid layer formation at some level when the restoration was placed after 10 days of the last bleaching session.
Keywords: Dental bleaching; Endodontically-treated tooth; Fracture strength; Hydrogen peroxide; Violet led